Personalized approach in the treatment of mental disorders: Long-term prospects for the use of low doses of psychotropic drugs. - Asanova Азізе (Psychosomatic Medicine and General Practice, 2020)
Importance. Despite the fact that in recent decades a large number of new psychotropic medication have been developed and investigated, psychotherapy and other treatments for mental disorders, it became apparent that many patients are resistant to treatment or response only after repeated changes in therapy or its combinations. Having a diagnosis of mental disorder itself was not sufficient to choose the best treatment. In the medical field, there is a new approach to the treatment of mental disorders - "personalized approach", which will treat not "diagnosis" but "patient". Materials and methods. In order to observe the prospects of using low doses of psychotropic drugs (and their combinations) to achieve more effective treatment results, a content analysis was conducted using Ukrainian and English publications for the last 15 years. The search was performed on the databases Pubmed, CrossRef. Results. The most effective drug is selected by the doctor based on the clinical condition and symptoms of the patient, but the most important factor in achieving successful results is the individually selected effective dose. Timely dose adjustment to achieve the desired clinical response, combined with the prevention of adverse reactions, is an important factor in maintaining patient’s adherence to treatment. Reducing the dose of psychotropic drugs to levels below those recommended in the instructions for use can lead to significant positive results due to: improved health care in general with more effective therapeutic results, reduced side effects and reduced patient`s costs. Personalized approach and judicious use of psychotropic drugs for other purposes is considered an integral part of the continuous development of science, taking into account the clinical experience of the use of drugs. Conclusions. There is a need to adjust the dosage of psychotropic drugs to the minimum effective dose that will meet the individual needs of the individual patient, and will help to find a balance between efficacy and risk of side effects and will be a necessary basis for developing an effective personalized approach in psychiatric practice. Optimizing the dosage of a psychotropic drug is an important factor in improving the efficiency of the health care system as a whole.